Dominance in data : a competition law perspective on data as a source of market power - Rentola, Tuomas (fi=Turun yliopisto|en=University of Turku|, 2017)
Technological development and the increasing number of people interacting with companies over the internet has led to an exponential increase in the amount of data. Even though data is used to develop and improve products and services in the digital economy, resulting in significant increases in consumer welfare, there is a growing concern over the concentration of data in the hands of a few companies. Market definition and market power are key concepts of competition law that can be applied consistently to new, emerging market phenomena. However, the dynamic nature of data-driven business models and the increasing importance of data in the competition between online platforms has forced competition law to expand to unchartered waters, prompting some commentators to even call for new tools to tackle the big data phenomenon. In order to advance the ongoing discussion about the intersection between competition law and data, this thesis explores whether and how the existing concepts of competition law are able to tackle concerns arising from the increasing concentration of data. In particular, this thesis is interested in investigating the fundamental question of whether and to what extent the concentration of data is a source of market power.